2022
DOI: 10.15407/ugz2022.01.047
|View full text |Cite
|
Sign up to set email alerts
|

Database of Paleosoil Research of the Holocene Within the Plains of Ukraine on the Basis of Gis Technology

Abstract: Today, the study of the development of Holocene nature and its individual components within the territory of Ukraine is quite active. The research results are reflected in dissertations and monographs as well as in numerous publications. But there is no separate generalizing scientific work linking all the available information. The aim of our work was the creation and maximum filling of the spatial database according to the results of paleosoil study of Holocene deposits of the plain territory of Ukraine on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The pedological analyses were carried out by Zh.M. Matviishyna and her students at several sites [43]. They revealed that buried soils, when preserved, belonged to several morphological types similar to those existing in the region today [21,22,44,45].…”
Section: State Of the Artmentioning
confidence: 99%
“…The pedological analyses were carried out by Zh.M. Matviishyna and her students at several sites [43]. They revealed that buried soils, when preserved, belonged to several morphological types similar to those existing in the region today [21,22,44,45].…”
Section: State Of the Artmentioning
confidence: 99%